2007
DOI: 10.1002/jbm.a.31402
|View full text |Cite
|
Sign up to set email alerts
|

Potential use of cholecalciferol polyethylene glycol succinate as a novel pharmaceutical additive

Abstract: D-alpha-tocopheryl polyethylene glycol succinate (TPGS) has been utilized in numerous drug delivery formulations in recent years. Because of its amphiphilic structure, it can be used as emulsifier and vehicle for lipid-based drug delivery formulations. It is also an effective P-glycoprotein (P-gp) inhibitor. However, TPGS represents only one of the surfactants in the class of "Vitamin-PEG" conjugated surfactants. To design a new adjuvant or additive, a conjugate made of vitamin D (cholecalciferol) and PEG-chol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…TPGS has been reported to inhibit P-gp-mediated drug resistance in MDR1 cDNA-transfected cells (G185) having 27–135-fold more resistance to cytotoxic drugs, thereby increasing cytotoxicity of DOX as compared to parental cells. In another study, cholecalciferol succinate has been reported to block P-gp and enhance accumulation of DOX ( p < 0.05) (28,49). …”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…TPGS has been reported to inhibit P-gp-mediated drug resistance in MDR1 cDNA-transfected cells (G185) having 27–135-fold more resistance to cytotoxic drugs, thereby increasing cytotoxicity of DOX as compared to parental cells. In another study, cholecalciferol succinate has been reported to block P-gp and enhance accumulation of DOX ( p < 0.05) (28,49). …”
Section: Discussionmentioning
confidence: 93%
“…Zhao et al used cholecalciferol–PEG succinate as an adjuvant in DOX-loaded PLGA nanoparticles and demonstrated its P-glycoprotein (P-gp) inhibitory potential (28). It has been reported that carboxylesterases present in tumor cells can efficiently convert various prodrugs into their active metabolites (43).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Выделили 60 мг (48 %) гемисукцината витамина D 3 . ЯМР спектр соответствует описанному в литературе [12]. Иммунизация.…”
Section: экспериментальная частьunclassified